(untitled) (International journal of artificial intelligence, 2025)
This article analyzes the role and significance of English proverbs in the process of language learning. English proverbs serve as an effective tool for enriching learners’ vocabulary, understanding figurative language, and developing communicative competence. The study highlights the semantic, cultural, and pedagogical aspects of proverbs and emphasizes their contribution to improving speaking skills and cultural awareness. In addition, the article discusses practical ways of integrating English proverbs into the language teaching process to enhance learners’ overall language proficiency.